MOSES AND THE COMMANDS OF GOD: The Role of Obedience to God's Commandments and Their Implications for the God’s People - Dapot Damanik; Ondrasi Gea; Rudi Ranto Siallagan; Rinawati Sitepu; Rosmina Berutu (Sekolah Tinggi Teologi Moriah, 2022)
God's commands are very beneficial for all mankind who believe in Him. However, in reality, more people refused and did not carry out the order. In the Bible, Moses is one of the recipients of God's commandment that at the beginning of his call he rejected the order. But finally he accepted and carried out God's command. Even though in the middle of the journey, Moses often complained and tried to refuse the order in leading the Israelites out of the land of Egypt due to the stubbornness of the people, sometimes Moses was affected by the situation so he violated His commands. The purpose of this article is to describe the journey of Moses receiving God's commands, since God revealed Himself to him and his ability to bring the Israelites out of Egypt to enter the land of Canaan by obedience to God's Commands. The method used in this article is to use a qualitative study research method with literature studies in the field of biblical theology. The discussion is focused on God's command to Moses in several important chronologies and how Moses' attitude towards God's command for the Israelites and how the attitude displayed by the Israelites responded to God's command. Perintah Allah sangatlah bermanfaat bagi semua umat manusia yang percaya kepadaNya. Namun kenyataannya lebih banyak yang menolak dan tidak melaksanakan perintah tersebut. Dalam Alkitab, Musa adalah salah satu penerima perintah Allah yang diawal panggilannya dia menolak perintah tersebut. Namun akhirnya dia menerima dan melaksanakan perintah Allah itu. Walaupun ditengah perjalanan sering sekali Musa mengeluh dan mencoba menolak perintah tersebut dalam memimpin bangsa Israel keluar dari tanah Mesir dikarenakan kedegilan bangsa tersebut, terkadang Musa terpengaruh oleh situasi sehingga melanggar perintahNya. Tujuan dari artikel ini adalah menggambarkan perjalanan Musa menerima perintah Allah, sejak Allah menyatakan diri kepadanya dan kemampuannya untuk membawa bangsa Israel keluar dari Mesir sampai menuju memasuki tanah Kanaan dengan ketaatannya kepada Perintah Allah. Adapun metode yang dipakai dalam artikel ini adalah menggunakan metode penelitian kajian kualitatif dengan studi literatur bidang teologi biblika. Pembahasannya difokuskan pada perintah Allah kepada Musa dalam beberapa kronologi penting serta bagaimana sikap Musa terhadap perintah Allah bagi bangsa Israel dan bagaimana sikap yang ditampilkan umat Israel menanggapi perintah Allah.